Answer:
c = -3
Step-by-step explanation:
Multiply all terms by the same value to eliminate fraction denominators
![4(-2)=4*\frac{-c-11}{4}](https://tex.z-dn.net/?f=4%28-2%29%3D4%2A%5Cfrac%7B-c-11%7D%7B4%7D)
Cancel multiplied terms that are in the denominator
![4(-2)=-c-11](https://tex.z-dn.net/?f=4%28-2%29%3D-c-11)
Multiply the numbers
![-8=-c-11](https://tex.z-dn.net/?f=-8%3D-c-11)
Add 11 to both sides of the equation
![-8+11=-c-11+11](https://tex.z-dn.net/?f=-8%2B11%3D-c-11%2B11)
Simplify
![3=-c](https://tex.z-dn.net/?f=3%3D-c)
Divide both sides of the equation by the same term
![\frac{3}{-1}=\frac{-c}{-1}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B-1%7D%3D%5Cfrac%7B-c%7D%7B-1%7D)
Simplify
![c=-3](https://tex.z-dn.net/?f=c%3D-3)
[RevyBreeze]
So there are two triangles here: Smaller one (ADE) and bigger one (ABC) and they both are similar.
So you can use proportions here.
AB / AC = AD / AE
AB = AD + DB = 6 + 1 = 7
AC = AE + 3
AD = 6
So plug in these values:
AB / AC = AD / AE becomes
7 / (AE + 3) = 6 / AE
Now do the cross multiply:
7 AE = 6 (AE + 3)
Now solve for AE:
7AE = 6AE + 18
AE = 18
Nmkndj;n;bnjngfndjknh;rtnh 216g6n
543646245mh.nrkjhgjn.kjgnrjkbuhjtbyultkngu;njktnj totm,my fotrtunanhioubgrviuebglryrhntonm my forytunabjvfdjkfvghyulbfwqlcbherovbegiunj gtjgbasyhj.bsf.fjkbgilhbjbhfljbvhuj